Comparison of Authority Between the State Administrative Court in Indonesia and the Mazhalim Institution in Islam - Asy‘ari, Asy‘ari; Ibrahim, Edwar (MAQASIDI: Jurnal Syariah dan Hukum, 2024)
The State Administrative Court in Indonesia is a judicial institution that is almost similar to the Mazhalim Institution in Islam. Although they have similarities, the two institutions have many differences in their concepts. This study aims to examine in more detail the comparison of the concept of authority of the State Administrative Court in Indonesia and Mazhalim institutions in Islam. This research is carried out through literature studies by collecting various literature from books, journals, and other documents related to the comparison of the concept of authority of the State Administrative Court in Indonesia and the Mazhalim Institution in Islam. The results of the study show that there are many differences between the State Administrative Court in Indonesia and the Mazhalim Institution in Islam, including that the PTUN in Indonesia has the authority of the Court to be on duty and has the authority to examine, decide, and resolve State Administrative disputes. State Administrative Disputes that occur between a citizen/community or civil legal entity and the State Administrative Agency/State Biocracy Official. The Mazhalim institution/court is authorized to examine, adjudicate, decide, and punish disputes that occur between the ruler and the people which includes ten cases. The Mazhalim institution has a wider authority not only in terms of cases that have the right to be tried but also regarding the authority to sentence and dismiss a person who is proven to have abused his position.